1991
DOI: 10.1093/intimm/3.12.1349
|View full text |Cite
|
Sign up to set email alerts
|

A novel subpopulation of CD45RA+ CD4+ T cells expressing IL-2 receptor α-chain (CD25) and having a functionally transitional nature into memory cells

Abstract: Differential expression of various isoforms of leukocyte common antigen (CD45), which arises from alternate mRNA splicing, identifies naive and memory populations of human T cells. Some memory (CD45RO+ CD45RA-) populations of CD4+ T cells from adult individuals express IL-2 receptor (IL-2R) alpha-chain (CD25), but naive (CD45RO- CD45RA+) CD4+ T cells only do so to a small degree. We found that a small but significant fraction of CD4+ T cells in neonatal blood expressed CD25, although most generally exhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…ϩ CD25 ϩ -regulatory T cells described by others (3)(4)(5)(6)(7)(8)33). Moreover, we have shown that CD4reg block CD8 ϩ T cells from responding to alloantigens and that this effect is only partially reversed by exogenous IL-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ϩ CD25 ϩ -regulatory T cells described by others (3)(4)(5)(6)(7)(8)33). Moreover, we have shown that CD4reg block CD8 ϩ T cells from responding to alloantigens and that this effect is only partially reversed by exogenous IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…One regulatory subset that has been well characterized expresses cell surface IL-2R ␣-chains (3,4). These CD4 ϩ CD25 ϩ T cells differentiate in the thymus and are exported to the periphery, where they suppress the activation of potentially self-reactive cells (3)(4)(5)(6)(7)(8). Injection of peripheral T cells from normal mice depleted of CD4 ϩ CD25 ϩ T cells into athymic mice results in a high incidence of organ-specific autoimmune disease (3,4).…”
mentioning
confidence: 99%
“…The lack of CD45RO expression has been described by all groups who have examined the phenotype of these cells in cord blood (34,37,39) and suggests that cord blood CD4 ϩ CD25 ϩ regulatory T cells are a naive (CD45RO Ϫ CD45RA ϩ ) population, contrasting with the memory (CD45RO ϩ CD45RA Ϫ ) population found in peripheral blood from adults. Similarly, far fewer cord than adult blood CD4 ϩ CD25 ϩ T cells express glutathione transferase (40).…”
Section: Cd38mentioning
confidence: 95%
“…Low IgG and IgA concentrations during infancy are partly explained by the deficient helper functions of CD4^ T cells in vivo. Namely, CD4'*" T cells from neonates and infants are predominantly CD45RA^ naive T cells and produce few ofthe cytokines required for production of IgG and IgA [12,24]. Our culture system provided these signals by adding CD62Lm emory CD4"^ T cells to PWM-stimulated cultures.…”
Section: Iga-and Iga2-producing Cells Induced In Neonatal and Adult Bmentioning
confidence: 99%
“…major cause of immune dysfunction during this period [7][8][9]. Neonatal T cells are unable to induce effective immunoglobulin class switch in B cells, because they virtually lack the CD45RO'*' (memory) subpopulation of 004"^ T cells [10][11][12]. In addition, neonatal B cells themselves are immature and produce only low levels of immunoglobulin even when the cells are stimulated by T-independent stimuli, such as Staphylococcus aureus Cowan I (SAC) and IL-2 [13].…”
Section: Introductionmentioning
confidence: 99%